Dredged marine sand as construction material - Limeir, Jussara; Agulló, Luis; Etxeberria, Miren (European journal of environmental and civil engineering, 2012)
This work deals with the study of dredged marine sand (DMS) from the Port of Sant Carles de la Ràpita (Tarragona, Spain) as construction material. The analysis of its influence on paste, mortar and concrete production is described. Two experimental phases were carried out after the chemical and physical characteristics of DMS were determined. Firstly, pastes and mortars were made using CEM II/A-M 42.5R cement, different percentages of DMS in replacement of raw sand and plasticiser additive in order to obtain the fresh and hardened properties of the mixes studied. After that, DMS was used for the production of concretes as fine aggregates. A pilot study was carried out with harbour concrete pavements produced at industrial scale. The results were compared to those of the control mixes and proved the satisfactory behaviour of DMS as construction material when incorporated into concrete as granular corrector Dans ce travail, l'étude d'un sable marin dragué DMS originaire du port de Sant Carles de la Ràpita (Tarragone, Espagne) comme matériau de construction est présenté. L'analyse de son influence sur des pâtes, mortiers et bétons est décrite. Deux phases expérimentales ont été effectuées après avoir déterminées les caractéristiques chimiques et physiques du DMS. Tout d'abord, des pâtes et des mortiers ont été réalisés en utilisant un ciment CEM II / AM 42.5R, avec différents pourcentages de remplacement du sable naturel par le DMS. L'utilisation des additifs plastifiants a été envisagée afin d'obtenir les propriétés requises aux états frais et durci des mélanges étudiés. Ensuite, le DMS a été utilisé comme granulats fins dans la fabrication de bétons. Une expérience pilote a été réalisée avec des pavements portuaires en béton produits à une échelle industrielle. Les résultats ont été comparés aux mélanges de contrôle et ont montré un comportement satisfaisant du DMS comme matériau de construction lorsqu'il est incorporé dans le béton comme correcteur granulaire.